Диаграммы направленности акустического излучения беспилотного летательного аппарата - Левский, Н. А.; Селезнев, И. С. (My University, 2021)
Methods for measuring the directional pattern of acoustic radiation of an unmanned aerial vehicle in acoustic systems for detecting and measuring coordinates of aircraft are considered. Examples and modifications of varieties of the main direction finding methods implemented using antenna arrays are considered. Shown are the main radiation patterns of unmanned aerial vehicles.
Keywords: БПЛА; акустическое излучение